MEKANİK VENTİLASYON UYGULAMASI SIRASINDA GELİŞEN NOSOKOMİYAL PNÖMONiLER - MEYANCI, Güniz; Öz, Hüseyin; MAMAL TORUN, Müzeyyen (Cerrahpaşa Medical Journal, 2019)
Background.- We aimed to point out pneumonia incidence in mechanically ventilated patients and define the prognosis and mortality rate in patients diagnosed to have pneumonia in Intensive Care Unit (ICU). Design.- In our study we re"1ewed 55 patients who were ventilated for at least 3 days and 28 patients out of 55, diagnosed to have pneumonia are included in the study. We verified pneumonia diagnosis according to infiltrations on chest X-ray and accompanying at least two clinical signs. For each patient studied, the chart is re"1ewed for the following parameters: ECG, invasive arterial pressure, central venous pressure, body temperature, microbiological analyses of tracheal aspirate, whole blood count, electrolyte, hemocultures, urine culture and pneumonic infiltration shown on chest X-ray. The antibiotic therapy schedule was devised as double or triple therapy according to antibiogram. Results.- Pneumonia incidence is found to be 50.6% and mortality incidence 61%. According to microbiological analyses of tracheal aspirates, S. aureus encountered in 7 cases, P. aeruginosa in 5 cases, enterococus'spp in 4 cases, acinetobacter'spp in 2 cases, Stenotrophomonas maltophilia in one case and H.influenzae in one case. In 7 cases polymicrobial pneumonia was the case. Conclusion.- Nosocomial pneumonia caused by polymicrobial and multiresistant microorganisms, appears as a disease with high mortality rate.